Scooby-Doo!. Happy Halloween, Scooby-Doo! [videorecording (DVD)] - Atoms, Maxwell, 1974- (Warner Bros. Home Entertainment, 2020)
It's a well-known fact that Halloween is Scooby's and Shaggy's favorite holiday. Why? Because it's the one day out of the year when the monsters are guaranteed to be fake (plus, there's free candy everywhere!) But, this year, their sweet holiday turns sour when the Spookiest monster they2ve ever met starts knocking on doors and scaring everybody out of town! Now it's up to Scooby and his pals to solve the mystery of this terrifying trick-or-treat and save the day!